Influence of distributed leadership on school effectiveness - Yangaiya, Salisu Abba; Mohd Ali, Hairuddin (International Journals of Multidisciplinary Research Academy (IJMRA), 2013)
The present study examines the relationship between distributed leadership (DL) and school effectiveness (SE), It examines which sub-scale of distributed leadership best explains school effectiveness. Questionnaires were used to get the needed data from secondary school teachers in Katsina state Nigeria. The questionnaires were adopted from Devis (2009) and Hulpia et al. (2010) and Oregon County Public Schools (OCPS), for distributed leadership inventory and school effectiveness scale respectively. Data was obtained from teachers of 227 sample schools. In all, 499 secondary school teachers sample was used in this study. Findings indicated that all the five subscales of distributed leadership predict school effectiveness. The predictors explained 48.4% variance of distributed leadership. Besides, it was revealed that principal leadership and participative decision making subscales, best predict school effectiveness.